IMPLEMENTASI SISTEM MANAJEMEN DALAM PENGOLAHAN DATA LAUNDRY STUDY KASUS “RICA UTAMI” - Kurniawan Wahyu Haryanto; Merlin Wahyu Supriati (SPIRIT, 2019)
Laundry is a business that is engaged in providing services, laundry work includes washing clothes, curtains, dolls and so forth. Rica Utami Laundry is a business that is engaged in laundry service providers founded by Ms. Rica Utami as the laundry business owner. At Rica Utami Laundry the data processing in this business is still using a manual process, from processing the laundry transaction data to making laundry transaction reports all of which are still processed in a book. This manual system is very inhibiting the processing of laundry data itself. Based on this problem, the authors raise a problem entitled "implementation of the management system in processing data laundry", making it easier for Rica Utami Laundry to see transaction report data every day even every month.Based on testing and analysis of results, it can be proven that this program is very helpful for the laundry especially the laundry business owner because the processing of data and reports can be done quickly with a computerized system. Keywords: Management System, Laundry, Rica Utami.